When identical twins are different. (18th April 2012) - Murray, A; Flood, K; Unterscheider, J; Barry, C; Geary, M; Breathnach, F; Malone, F
Abstract : Background: Classically monozygotic (MZ) twins are considered identical. However, there are a number of cases of MZ twins concordant for genotype but not phenotype. A review of these cases was performed in our institution. Methods: Patients who had monozygotic twin pregnancies with discordant anomalies but normal karyotype were identified from the Fetal Assessment Unit Database of the Rotunda Hospital between January 2006 and July 2011. A retrospective chart review was then performed. Results: Fifteen pairs of monozygotic twins who were genotypically identical but phenotypically different were identified. Average maternal age was 28.6 years. 93% were spontaneously conceived and all had ultrasound assignment of chorionicity prior to 16 weeks gestation. Discordant anomalies detected by ultrasound included two cystic hygromas, one duodenal atresia, three spinal abnormalities, three cerebral abnormalities one Congenital Diaphragmatic Hernia, two Gastroschisis, one bilateral hydronephrosis, one single vessel cord and one twin with a two vessel cord. 73% confirmed normal karyotype with invasive testing. Two patients underwent laser ablation of connecting vessels and this was associated with intrauterine demise of the affected twin. Regarding outcomes of the other pregnancies, three had intrauterine death of both twins. The twin with CDH had an early neonatal death. Conclusion: This is an interesting series which highlights the non-identical nature that can occur in monozygotic twin pregnancies. Emerging data shows that there are different types of genetic/epigenetic and prenatal post-zygotic mechanisms that can cause discordance within such twin pairs. This possibility should be included in counselling patients with monozygotic pregnancies.